Idiopathic Intracranial Hypertension in the United States: Demographic and Socioeconomic Disparities - Ghaffari-Rafi, Arash; Mehdizadeh, Rana; Ko, Andrew Wai Kei; Ghaffari-Rafi, Shadeh; Leon-Rojas, Jose (Frontiers in Neurology, 2020)
Background Obesity’s risk increases for low income, female, young, and Black patients. By extrapolation, idiopathic intracranial hypertension (IIH)—a disease associated with body mass index—would potentially display socioeconomic and demographic disparities. Methods IIH incidence (per 100,000) was investigated with respect to sex, age, income, residence, and race/ethnicity, by querying the largest United States (US) healthcare administrative dataset (1997-2016), the National (Nationwide) Inpatient Sample (NIS). Results Annual national incidence (with 25th and 75th quartiles) for IIH was 1.15 (0.91, 1.44). Females had an incidence of 1.97 (1.48, 2.48), larger (p = 0.0000038) than males at 0.36 (0.26, 0.38). Regarding age, largest incidence was amongst those 18-44 years old at 2.47 (1.84, 2.73). Low income patients had an incidence of 1.56 (1.47, 1.82), larger (p = 0.00024) than the 1.21 (1.01, 1.36) of the middle/high. No differences (χ^2 = 4.67, p = 0.097) were appreciated between urban (1.44; 1.40, 1.61), suburban (1.30; 1.09, 1.40), or rural (1.46; 1.40, 1.48) communities. For race/ethnicity (χ^2 = 57, p = 2.57 x 10^(-12)), incidence was largest for Blacks (2.05; 1.76, 2.74), followed by Whites (1.04; 0.79, 1.41), Hispanics (0.67; 0.57, 0.94), and Asian/Pacific Islanders (0.16; 0.11, 0.19). Year-to-year, incidence rose for all strata subsets except Asian/Pacific Islanders (τ = -0.84, p = 0.00000068). Conclusion IIH demonstrates several sociodemographic disparities. Specifically, incidences are larger for those low income, Black, 18-44 years old, or female, while annually increasing for all subsets, except Asian/Pacific Islanders. Hence, IIH differential afflicts the US population, yielding in healthcare inequalities.